Genetics of a Transgenic Beetle (Tribolium castaneum) Carrying Green Fluorescent Protein - Milholm, Matthew; Park, Yoonseong (My University, 2017)
We found that a transgenic line of Tribolium castaneum, previously characterized for the expression of green fluorescent protein (GFP) in the oenocyte (OE strain), shows unusual genetics based on the GFP expression patterns. The larval individuals of OE line showed GFP expressions are not homogeneous among individuals; the expressions are in their oenocyte or hindgut, or in both organs. We provide two alternative hypotheses for this phenomenon: H1) variable expressions of a GFP gene in different stages or H2) more than one GFP transgenes. We tested this hypotheses by examining the GFP expression patterns in larval stages over the period of one week. In addition, we crossed the OE line to wildtype to understand the segregation pattern of the GFP phenotypes. We found that the GFP expression pattern in the OE changes within a molting instar leading to an conclusion accepting the H2) variable expressions of a GFP transgene in OE line, while the genetic crossing is in progress to test the H1) multiple GFP transgene insertions.